Alkoxylation Followed by Iodination of Oxindole with Alcohols Mediated by Hypervalent Iodine Reagent in the Presence of Iodine. Issue 33 (17th August 2018) - Kotagiri, Rajendraprasad; Adepu, Ramesh
Abstract : Oxidative coupling of oxindole with alcohols followed by in situ iodination by using a PhI(OCOCF3 )2 /I2 system afforded 5‐iodo‐3‐monoalkoxy and 5‐iodo‐3, 3‐di alkoxyoxindole in moderate to good yields. This method provides a new and transition metal‐free synthesis of iodoalkoxy‐substituted oxindoles in one pot from readily available oxindole under mild conditions. Abstract : Iodoalkoxylation of oxindole with alcohols was achieved by using a hypervalent iodine species in combination with iodine under metal‐free conditions. This method is useful for the synthesis of 3‐alkoxy oxindole, 5‐iodo‐3‐alkoxy oxindole and 5‐iodo‐3, 3‐dialkoxy oxindole by sequentially in moderate to good yields.